Frank Simon: A personal story about everyday educational realities - Braster, Sjaak; del Pozo Andrés, María del Mar (Historia y Memoria de la Educación, 2018)
Frank Simon (1944) is an Emeritus professor of History of Education in Ghent University from the year 2009. Internationally he is known by a large group of scholars because of his involvement with the journal Paedagogica Historica and the role he played inside the International Standing Conference for the History of Education (ISCHE). In this article he speaks about some personal events that have shaped his life, and about the people that have inspired him during his academic career. He also gives his views on the future of the history of education as a discipline, and the historical work that still must be done.